HUBUNGAN PENGORGANISASIAN PROGRAM TERHADAP KINERJA PAMONG BELAJAR PADA SANGGAR KEGIATAN BELAJAR - R. Lumapow, Harol (Jurnal Cakrawala Pendidikan, 2015)
Abstract: The Relationship between the Program Organization and the Learning Tutors’ Performance in Learning Activity Workshops. This study aims to investigate the functional relationship between learning tutors’ motivation, supervision intensity, program organization, and learning tutors’ work performance. This study was a survey using a correlational method. The sample, consisting of 63 learning tutors, was randomly selected. The results show that there is a positive correlation between: (1) program organization and learning tutors’ work performance of with r = 0.84; (2) work motivation and learning tutors’ work performance of with r = 0.77; and (3) supervision intensity and learning tutors’ work performance of with r = 0.68. The regression equation is í = 0,58X1 + 0,47X2 + 0.42X3 – 29.73. Keywords: program organization, work motivation, supervision intensity, learning tutors’ work performance